Strongyloides—An uncommon cause of eosinophilia whilst on durvalumab - Gaik Tin Quah; Gillian Blanchard; Neil Miller; Paul Wilson; Ina Nordman (Cancer Reports, 2022)
Abstract Background In malignancy, eosinophils have been shown to play an important role in the tumour micro‐environment. Increasingly, development of eosinophilia with immune checkpoint inhibitor (ICI) use is thought to be predictive of prognosis and development of immune‐related adverse events. However, there are many other causes for developing eosinophilia which can contribute to the difficulties in diagnosis and management. Case Here, we present a case of Strongyloides parasitic infection as an uncommon differential for eosinophilia in a patient with lung cancer receiving a PDL‐1 ICI, durvalumab, in Australia. Conclusion This case highlights the complexities exploring the multiple potential causes of eosinophilia and the subsequent management, to allow safe continuation of ICI.